Βιβλιοκρισία: M. D. LAUXTERMANN, Byzantine poetry from Pisides to Geometres. Texts and contexts. Volume two (WBS 24/2), Βιέννη 2019 - ΧΡΥΣΟΓΕΛΟΣ Κωνσταντίνος (Byzantina Symmeikta, 2022)
Βιβλιοκρισία: M. D. Lauxtermann, Byzantine poetry from Pisides to Geometres. Texts and contexts. Volume two (WBS 24/2), Βιέννη 2019